Effectiveness of an Instructional Program Concerning Secondary Polycythemia Knowledge on Clients Attending Iraqi National Blood Bank - Huda Baker Hassan; Abbas Labeeb Wadi (Kufa Journal for Nursing Sciences)
Background: Secondary Polycythemia (SP) mean an elevated of erythrocytes numbers and hemoglobin above normal levels which as more than 18 g / liter in males or 16 g / liter in females, and the elevated red blood cell above the normal level lead to many complication as thromboembolisim, hypertension, and gout.